Baseline Description of the Juvenile Localized Scleroderma Subgroup From the Childhood Arthritis and Rheumatology Research Alliance Legacy Registry. Issue 2 (10th April 2019) - Wu, Eveline Y.; Li, Suzanne C.; Torok, Kathryn S.; Virkud, Yamini V.; Fuhlbrigge, Robert C.; Rabinovich, C. Egla; ,
Abstract: Objective: Localized scleroderma (LS) is a chronic inflammatory and fibrosing skin disorder. We present baseline data on the juvenile LS (jLS) cohort from the Childhood Arthritis and Rheumatology Research Alliance (CARRA) Legacy Registry, a multicenter observational registry of pediatric rheumatologic disorders. Methods: This is a cross‐sectional analysis of children with jLS enrolled in the CARRA Legacy Registry between May 2010 and April 2014. Descriptive statistics were used for demographic, clinical, and laboratory features. Data analysis included two‐sample t test, χ 2 test, Fisher's exact test, linear/logistic regression, and analysis of variance. Results: Of 381 children with jLS, 76% were female and 80% Caucasian. Mean onset age was 8.2 years, with 17% having a 2‐year or greater delay to first pediatric rheumatology (PRH) visit. Linear scleroderma was the most common subtype (54%). Antinuclear antibody (ANA) positivity was associated with joint contracture ( P = 0.04), muscle atrophy ( P = 0.014), and extremity shortening ( P = 0.007). Elevated aldolase was associated with joint contracture ( P = 0.008) and elevated creatine kinase (CK) with muscle atrophy ( P = 0.028) and extremity shortening ( P = 0.016). Children with functional limitation (27%) had earlier first PRH visit compared with those without ( P = 0.01). Poorer function correlated with muscle atrophy, joint contracture, and extremity shortening ( P < 0.001). Methotrexate (97%) and corticosteroids (68%) were the most common medications used. Conclusion: Children with jLS without joint limitation are referred later, highlighting the insidious onset and need for educating referring providers. Poorer function correlated with muscle atrophy, joint contracture, and limb shortening. ANA positivity and elevated CK or aldolase were associated with muscle atrophy, joint contracture, and/or limb shortening, suggesting predictors of muscle involvement.